1998
DOI: 10.1143/jjap.37.2007
|View full text |Cite
|
Sign up to set email alerts
|

Stabilized Platinum Electrodes for Ferroelectric Film Deposition using Ti, Ta and Zr Adhesion Layers

Abstract: Pt-based metallizations using different adhesion layers (Ti, Zr and Ta) were studied for use as electrodes for ferroelectric thin films on oxidized silicon substrates. Different ways of oxidizing the adhesion layers prior to ferroelectric film growth are compared, with regard to obtaining stable, adherent Pt films of well-defined (111) orientation, while avoiding lead diffusion through the electrode. Upon in-situ deposition of PbTiO 3 at high excess lead flux, lead diffusion through the Pt film was found to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(58 citation statements)
references
References 17 publications
(28 reference statements)
4
54
0
Order By: Relevance
“…Previously, a similar but much stronger density decrease of the Pt layer in Pt/ Ti bilayer electrode upon the annealing was reported and attributed to the strong diffusion of Ti and its following oxidation. 21,22 Though the diffusion at the Pt/ TiO x interface was not strong 6,11 or even undetectable as reported, 18 the limited diffusion and incorporation of Ti and O into Pt have been observed previously [23][24][25][26] and confirmed by scanning transmission electron microscopy. 16 Ti and O can migrate along the grain boundaries of Pt when the sample is annealed.…”
Section: A Formation Of Pt Hillocks On the Bare Pt Electrodesupporting
confidence: 61%
See 1 more Smart Citation
“…Previously, a similar but much stronger density decrease of the Pt layer in Pt/ Ti bilayer electrode upon the annealing was reported and attributed to the strong diffusion of Ti and its following oxidation. 21,22 Though the diffusion at the Pt/ TiO x interface was not strong 6,11 or even undetectable as reported, 18 the limited diffusion and incorporation of Ti and O into Pt have been observed previously [23][24][25][26] and confirmed by scanning transmission electron microscopy. 16 Ti and O can migrate along the grain boundaries of Pt when the sample is annealed.…”
Section: A Formation Of Pt Hillocks On the Bare Pt Electrodesupporting
confidence: 61%
“…However, the Pt/ Ti metallic electrode shows poor thermal stability and reliability including the formation of Pt hillocks [5][6][7][8] or bumps under thermal conditions, 9 surface morphology evolution during aging, 7 short circuit of ferroelectric capacitors caused by the Pt hillocks, 10 severe diffusion of Ti into Pt, and even encapsulation of Pt hillocks with TiO x during annealing. 6,[9][10][11] In contrast, Sreenivas et al reported that the Pt/ TiO x electrode structure shows an improved thermal stability. 6 For a given ferroelectric medium with a certain chemistry and structure, the ferroelectricity is dependent on the electrical and mechanical boundary conditions to a great extent.…”
Section: Introductionmentioning
confidence: 99%
“…As Cr 2 O 3 is found both below and above Ru, one can conclude that Ru is neither a good barrier against oxygen, nor against Cr diffusion. This might be generalized to any noble metal / reactive metal stack: in a recent paper [20], we show the oxidation behavior of Ti, Zr and Ta adhesion layers for Pt metallizations (whether the adhesion layer oxidizes in and above the Pt or below it) is determined by the respective cation and oxygen mobilities in the corresponding oxide. Finally, one should note that pure Cr was chosen rather than an alloy for simplicity in this study.…”
Section: Discussionmentioning
confidence: 84%
“…The difference in behavior might be understood when one knows that in the oxide Ti diffuses more than oxygen while Ta diffuses slower than oxygen. 9 In a previous study, 9 we showed that when one oxidizes the electrode (without depositing the PZT), almost all the Ti comes to the Pt surface while most of the tantalum stays under the Pt. In the case of Ti, there is upward diffusion of Ti, which leaves a lot of vacancies and voids, which are at least partially filled by downward diffusion of oxygen, lead and Pt.…”
Section: Discussionmentioning
confidence: 95%